PENENTUAN KECEPATAN PENGENDAPAN UNTUK MERANCANG UNIT PENGENDAP NATRIUM BENTONIT - Siti Isnijah S.P.; Tasrif Tasrif; Nuryatini Nuryatini (Jurnal Kimia Terapan Indonesia, 1997)
One step of producing paint additive from bentonite is to change Ca-beruonite into Na-bentonite. It applied ion-exchange process by using saturated solution of NaCl. Purification of product was done by washing to remove excess of salt. Nabentonite in production capacity of 40 kg could be separated from water by decantation. Observing the performance of precipitation rate of No-bentonite gave technical data for designing of precipitation unit. The precipitation of Na-bentonite in laboraroty scale was conducted using glass columns with diameter of 2.7 cm; 4.7 cm; 6.2 cm and 11.5 cm respectively. Height of slurry in column was varied in a range of 0.1 m ; 0.2 m ; 0.4 m and 1.0 m. The higher "slurry height" gave a faster precipitation rate. However, in term of separation efficiency determined as percentage of supernatant removed from slurry, higher slurry height resulted lower efficiency. At slurry height of 0.2 m, water removed were 72% (v/v) and 45% (v/v) in 30 minutes for first and second washing processes respectively. By second washing lower volume of supernatant was removed due to the characteristic of Nabentonite that swells during washing process.